2016
DOI: 10.1177/1087054716676364
|View full text |Cite
|
Sign up to set email alerts
|

Overweight in Boys With ADHD Is Related to Candidate Genes and Not to Deficits in Cognitive Functions

Abstract: Overweight in boys with ADHD is associated with polymorphisms in three candidate genes: DRD4, SNAP25, and 5HTR2A, but not through conditioning deficits in cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
(66 reference statements)
2
12
1
Order By: Relevance
“…As BMI is dependent on gender and age, in assessing overweight and obesity we used a diagnostic method adjusted for age and gender. The most prevalent presentation/subtypes of ADHD were the combined type (75.7%), followed by the ADHD inattentive (17.3%) and ADHD hyperactive-impulsive types (7.0%), which is consistent with earlier observations [60,61]. Similarly, in other recorded characteristics such as comorbidity [57] or the socioeconomic status of the family [62], our patients did not differ from the previously observed clinical groups [63].…”
Section: Discussionsupporting
confidence: 91%
“…As BMI is dependent on gender and age, in assessing overweight and obesity we used a diagnostic method adjusted for age and gender. The most prevalent presentation/subtypes of ADHD were the combined type (75.7%), followed by the ADHD inattentive (17.3%) and ADHD hyperactive-impulsive types (7.0%), which is consistent with earlier observations [60,61]. Similarly, in other recorded characteristics such as comorbidity [57] or the socioeconomic status of the family [62], our patients did not differ from the previously observed clinical groups [63].…”
Section: Discussionsupporting
confidence: 91%
“…Another study set out to test, in a sample of 109 boys with ADHD (7–17 years), the relationship between overweight, polymorphism in selected genes, and cold executive dysfunctions expected to lead to abnormal eating patterns via impulsivity and inattention [27]. Tests used to investigate the executive functions included: Continuous Performance Test, Stroop Colour–Word Interference Test, Trail Making Test A and B, Matching Familiar Figures Test, Verbal Fluency Test, Rey–Osterrieth Complex Figure Test and Wisconsin Card Sorting Test.…”
Section: What Are the Factors Underpinning The Association Betweenmentioning
confidence: 99%
“…Other studies published so far have shown that children with ADHD have increased body weight or BMI in comparison with pediatric norms or control groups [6,13,20,36]. Holtkamp et al found that boys with ADHD had higher BMI and were more often overweight or obese compared to the general population [10].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies show that ADHD is a risk factor for obesity independently of pharmacological treatment, socio-economic status, and most of the other disorders accompanying ADHD. The link between ADHD and obesity becomes more pronounced with age, from a slight correlation in toddlers with ADHD to a high frequency of obesity in adults with ADHD [12,13]. However, in relation to the general population, international studies have reported that the number of persons with overweight and obesity almost tripled in the last 40 years [14].…”
Section: Introductionmentioning
confidence: 99%